2015
DOI: 10.1074/jbc.m115.655555
|View full text |Cite
|
Sign up to set email alerts
|

Retinylamine Benefits Early Diabetic Retinopathy in Mice

Abstract: Background:The development of diabetic retinopathy (DR) is incompletely understood. Administered retinylamine is stored in the retinal pigmented epithelium (RPE) where it affects the ocular visual cycle. Results: Retinylamine inhibited vascular and neural lesions of early DR. Conclusion: Both the RPE and visual cycle are novel targets for the inhibition of DR. Significance: Vision-related processes can contribute to DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 79 publications
1
57
0
Order By: Relevance
“…For patients with Stargardt disease wherein A2E is thought to be a primary contributor to macular degeneration (Sparrow and Boulton, 2005;Moiseyev et al, 2010;Charbel Issa et al, 2015;Saad and Washington, 2016), direct RPE65 inhibition by emixustat-like molecules could be therapeutically advantageous, as it was previously reported that both emixustat and its predecessor retinylamine lower A2E formation in mouse models of Stargardt disease (Maeda et al, 2011;Bavik et al, 2015). These compounds also exert beneficial effects in mouse models of diabetic retinopathy thought to be related to their ability to inhibit RPE65 (Liu et al, 2015). Improving visual cycle modulator potency could lessen any off-target side effects.…”
Section: Rdh8mentioning
confidence: 91%
“…For patients with Stargardt disease wherein A2E is thought to be a primary contributor to macular degeneration (Sparrow and Boulton, 2005;Moiseyev et al, 2010;Charbel Issa et al, 2015;Saad and Washington, 2016), direct RPE65 inhibition by emixustat-like molecules could be therapeutically advantageous, as it was previously reported that both emixustat and its predecessor retinylamine lower A2E formation in mouse models of Stargardt disease (Maeda et al, 2011;Bavik et al, 2015). These compounds also exert beneficial effects in mouse models of diabetic retinopathy thought to be related to their ability to inhibit RPE65 (Liu et al, 2015). Improving visual cycle modulator potency could lessen any off-target side effects.…”
Section: Rdh8mentioning
confidence: 91%
“…73 However, in a separate study, we did not find that diabetes altered all-transretinaldehyde levels compared to that in age-matched nondiabetic mice. 75 Also little or no photoreceptor death has been reported in the diabetic mouse model. 6 Diabetes does, however, result in activation of retinal NADPH oxidase because apocynin can correct the diabetes-induced lesions.…”
Section: Discussionmentioning
confidence: 99%
“…More important, this therapy, which acts in the RPE, also inhibited retinal lesions that are clinically relevant in DR (degeneration of retinal capillaries and increased permeability). 59 The available data suggest that RPE cells and possibly also the visual cycle contribute to the development of DR. Neither the RPE nor enzymes of the visual cycle have previously been identified as potential contributors to the pathogenesis of DR or as potential targets for therapeutic inhibition of DR.…”
Section: Rpe Datamentioning
confidence: 99%
“…59 Retinylamine is an analog of vitamin A that is selectively retained by only two tissues in the body, RPE and liver. It is an effective trap for reactive aldehydes, and is known to inhibit the RPE-specific protein 65 kDa, 85,86 an enzyme of the visual cycle that converts alltrans-retinol esters back to 11-cis-retinal.…”
Section: Rpe Datamentioning
confidence: 99%